PENGELOLAAN PERPUSTAKAAN PERGURUAN TINGGI BERBASIS KONSEP INSTITUTIONAL REPOSITORY - Yanto Yanto (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
Management of Institutional Repository (IR) in the University Library is related to important issues in the application of technology in the library that carries a very significant change from a computerized based system library services (library automation), to change the storage form of printed to digital collections. Activities that collect and preserve digital collections which are the result of intellectual work of a community called the IR. IR Management in University Libraries view several aspects: the readiness of the infrastructure (software and hardware), readiness of human resources and the implementation of policies. Besides the management of IR University Library is constituted by three things, namely, IR as the archive, storage IR is used to ease the access and IR imaging is used as a means of institutions image. IR Management University Library can be done through several factors: their mandate / legitimacy, their integrated planning with center institutions, a transparent funding, the digitalization program, interoperability, evaluation and measurement, as well as the promotion of their digital preservation strategy.